PathÃÂªt: Ruang Bunyi dalam Karawitan Gaya Yogyakarta - Budi Prasetya, Hanggar (PANGGUNG, 2012)
This research aims to answer a question of why two Javanese gamelan pieces (gending) of differ- ent pathÃÂªt (modes) cannot be performed consecutively without grambyangan lead. The data of this research were obtained from in-depth interview and observation of karawitan (gamelan performanc- es), focusing on karawitan training process, wayang performances, and karawitan performances for pleasure or uyon-uyon. Using phenomenology method, it can be concluded that pathÃÂªt is a space of sound. Two gamelan pieces having different modes are similar to two gamelan pieces in different spaces. There is a link between spaces that can be opened by the sound of gender or grambyangan. As a space, karawitan has three spaces of sound, i.e. space of pathÃÂªt nem, space of pathÃÂªt sanga, and space of pathÃÂªt manyura.ÃÂ Keywords: gending, pathÃÂªt, ruang bunyi, karawitan Jawa.